Financial Legal Risks and Prevention Mechanisms in Cross-Border Mergers and Acquisitions: A Systemic Analysis - Yiding Liang (Law and Economy, 2025)
This study examines critical financial legal challenges in cross-border mergers and acquisitions (M&A) within the context of increasing global economic integration. Through multi-jurisdictional case analysis and comparative legal research, it reveals systemic vulnerabilities stemming from regulatory disparities, financing constraints, and currency volatility across different legal frameworks. The investigation identifies three primary risk clusters: transactional risks arising from information asymmetry during due diligence, compliance risks associated with conflicting financial regulations, and post-merger integration risks involving cross-border capital management. Current prevention mechanisms demonstrate limited effectiveness due to fragmented risk management approaches and reactive strategies. A comprehensive prevention framework is proposed, integrating pre-transaction risk assessment protocols, dynamic monitoring systems for capital flows, and standardized compliance mechanisms adaptable to diverse legal environments. The framework emphasizes proactive risk identification through enhanced information-sharing channels between financial institutions and regulatory bodies, coupled with intelligent early-warning systems for financial compliance monitoring. Implementation pathways suggest establishing transnational coordination mechanisms and specialized risk assessment tools tailored for small-to-medium enterprises engaged in cross-border transactions. Findings indicate that adopting this integrated approach could substantially improve risk mitigation capabilities while maintaining operational flexibility. The research contributes practical insights for enterprises navigating complex cross-border transactions and provides policy recommendations for harmonizing international financial regulatory standards. Future studies should focus on digital compliance solutions and adaptive legal frameworks for emerging financial instruments in M&A activities.